The Urgency of Yellowislamic Book Learning Innovation in Pesantren: A Case Study of the Minikom Dormitory at PP Mambaul Ulum Bata-Bata - Sari Nusantara Putri (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2024)
This study analyzes the effectiveness of educational management in the Minikom dormitory of Pondok Pesantren Mambaul Ulum Bata-Bata, focusing on its influence on student learning outcomes. The main variables are educational management practices—planning, implementation, and supervision—and their relationship to the effectiveness of learning in the boarding school environment. The study uses a qualitative approach to explore these dynamics, as this method allows for an in-depth understanding of contextual and organizational practices. Data were collected through interviews, observation, and document analysis involving dormitory leaders, educators, and students. Findings reveal that educational management in the Minikom dormitory follows a structured planning process, consistent program implementation, and integrated supervision. These elements contribute to fostering student engagement and improving learning effectiveness. The study underscores the significance of coherent management strategies in enhancing educational outcomes within Islamic boarding school settings.